Lacan and the male homosexuality - Cruxên, Orlando (Revista de Psicologia, 2013)
The presente articleisan approach about Jaques Lacan’sconceptions on malehomosexuality, which were presented in theSeminar, Book V, The formations o f the unconscious. It considers the theoretic paradigmas about the themeas described in the mentioned work, which brings also some of Freudian theories on the subject. Besides, the article stresses some problematic considerations without forma laccuracy, what means a biased approach of the theme.